An epidemiological study of cervical and breast screening in India: district-level analysis - Monica; Raman Mishra (BMC, 2020)
Abstract Background Breast cancer and cervical cancer, the most common forms of cancer in women worldwide, are on a fast and steady rise, accounting for more deaths in women than any other cancer in the developing world. Cancer screening tests are an important tool to combat cancer-related morbidity and mortality. World Health Organization aims to accelerate action to achieve Goal 3.4 of the Sustainable Development Goals (SDG 3.4) in order to reduce premature mortality from non-communicable disease, including cancer by one-third by 2030. This study aims to examine the geospatial variation of cervical and breast screening across districts and to identify factors that contribute to the utilization of screening among women in India. Methods Until recently, there was no evidence pertaining to screening for cervical and breast cancers at the national level. Information on examination of the breast and cervix from over 699,000 women aged 15-49 years was collected for the first time in the fourth round of National Family Health Survey, 2015-16 (NFHS-4). For the present study, the data were aggregated for all 640 districts in India. Moran's Index was calculated to check for spatial autocorrelation. Univariate Local Indicators of Spatial Association (LISA) maps were plotted to look for spatial dependence associated with the uptake of screening practices. The spatial error model was employed to check for spatial magnitude and direction. Results The common factors associated with uptake of both cervical and breast screening at the district level were; women belonging to a general caste, residing in rural areas, being currently married, and being well-off economically. Being insured was positively associated with the uptake of cervical screening only. This study provides spatial inference by showing geographical variations in screening of cervix and breast across districts of India. Conclusions By showing geographical disparities in screening practices across districts of India, this study highlights the importance of ensuring a region-specific and organ-specific approach towards control and prevention of cancer. The identified factors responsible for the uptake of screening could be a guiding force to decide how and where tailored interventions may be best targeted.